2015
DOI: 10.1111/maps.12392
|View full text |Cite
|
Sign up to set email alerts
|

A partial melting study of an ordinary (H) chondrite composition with application to the unique achondrite Graves Nunataks 06128 and 06129

Abstract: Melting experiments of a synthesized, alkali‐bearing, H‐chondrite composition were conducted at ambient pressure with three distinct oxygen fugacity conditions (IW‐1, IW, and IW+2). Oxygen fugacity conditions significantly influence the compositions of partial melts. Partial melts at IW‐1 are distinctly enriched in SiO2 relative to those of IW and IW+2 melts. The silica‐enriched, reduced (IW‐1) melts are characterized by high alkali contents and have silica‐oversaturated compositions. In contrast, the silica‐d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 55 publications
3
28
0
Order By: Relevance
“…The composition of the secondary olivine might be also controlled by the oxygen fugacity ( f O 2 ) in the melt, as constrained in melting experiments for ordinary chondrite (Usui et al. ). However, effects induced by variation of f O 2 are relatively negligible for the Fe 3+ /Fe 2+ ratio in olivine (e.g., Putirka ).…”
Section: Discussionmentioning
confidence: 99%
“…The composition of the secondary olivine might be also controlled by the oxygen fugacity ( f O 2 ) in the melt, as constrained in melting experiments for ordinary chondrite (Usui et al. ). However, effects induced by variation of f O 2 are relatively negligible for the Fe 3+ /Fe 2+ ratio in olivine (e.g., Putirka ).…”
Section: Discussionmentioning
confidence: 99%
“…Usui et al. () studied low pressure experimental partial melting of a H chondrite analog which showed that siliceous (quartz‐normative) melts can be formed by very small degrees of melting under reducing conditions. Experimental studies by Gardner‐Vandy et al.…”
Section: Discussionmentioning
confidence: 99%
“…Other achondrites are derived from parent bodies with f O2 that are not well defined (e.g., brachinites, unclassified Na-rich achondrites such as GRA 06129/06128). As has been demonstrated, differences in the f O2 (IW-1 to IW+2) during partial melting on these parent bodies will produce considerably different melt compositions (e.g., Jurewicz et al 1995;Gardner-Vandy et al 2013;Usui et al 2015). Several studies have linked brachinites to unique sodium feldspar-rich achondrite GRA 06129/06128 (e.g., Shearer et al 2010;Usui et al 2015).…”
Section: Spinels As Indicators Of Planetary Parentage and Redox Histomentioning
confidence: 95%
“…As has been demonstrated, differences in the f O2 (IW-1 to IW+2) during partial melting on these parent bodies will produce considerably different melt compositions (e.g., Jurewicz et al 1995;Gardner-Vandy et al 2013;Usui et al 2015). Several studies have linked brachinites to unique sodium feldspar-rich achondrite GRA 06129/06128 (e.g., Shearer et al 2010;Usui et al 2015). Usui et al (2015) illustrated that partial melting of a chondritic precursor would yield a brachinite residuum and a GRA 06129 melt, under specific f O2 conditions.…”
Section: Spinels As Indicators Of Planetary Parentage and Redox Histomentioning
confidence: 95%
See 1 more Smart Citation